2022
DOI: 10.1186/s12933-022-01579-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of symptoms, comorbidities, fibrin amyloid microclots and platelet pathology in individuals with Long COVID/Post-Acute Sequelae of COVID-19 (PASC)

Abstract: Background Fibrin(ogen) amyloid microclots and platelet hyperactivation previously reported as a novel finding in South African patients with the coronavirus 2019 disease (COVID-19) and Long COVID/Post-Acute Sequelae of COVID-19 (PASC), might form a suitable set of foci for the clinical treatment of the symptoms of Long COVID/PASC. A Long COVID/PASC Registry was subsequently established as an online platform where patients can report Long COVID/PASC symptoms and previous comorbidities. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
154
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 155 publications
(173 citation statements)
references
References 59 publications
13
154
0
6
Order By: Relevance
“…The demographics, serum ferritin and IL-6 levels performed on the day of blood collection, self-reported symptom analysis and comorbidities before suffering from acute COVID-19 of our long COVID patients and controls are shown in Table 1 below. Our results follow trends reported on previously [34,35]. Interestingly, previously it has beenreported that misfolded protein aggregates behave as infectious agents [36].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The demographics, serum ferritin and IL-6 levels performed on the day of blood collection, self-reported symptom analysis and comorbidities before suffering from acute COVID-19 of our long COVID patients and controls are shown in Table 1 below. Our results follow trends reported on previously [34,35]. Interestingly, previously it has beenreported that misfolded protein aggregates behave as infectious agents [36].…”
Section: Resultssupporting
confidence: 92%
“…Figure 2 shows activated platelets and fibrin amyloid microclots present in representative blood samples from the current cohort. This was in line with the findings of our previous papers [1,17,34,35].…”
Section: Demographicssupporting
confidence: 93%
“…We note that aberrant platelet activation and fibrin amyloid microclots have recently been reported in patients with Long COVID (Pretorius et al, 2022) as well as in ME/CFS patients, though the microclot load was found to be less in the ME/CFS cohort (Nunes et al, 2022). These studies correspond most closely to the baseline state assessed here, and our results also suggest that dysregulation, as judged by transcriptome analysis, occurs at baseline.…”
Section: An Abnormal Platelet State Is Coincident With Pem In Me/cfssupporting
confidence: 86%
“…( C , D) Representative micrographs of microclots in plasma from acute COVID-19 participants (taken from raw data as in [ 87 ]). ( E ) Representative micrograph of microclots in plasma from participants with Long COVID (taken from raw data in [ 422 ]).…”
Section: Size Of Fibrin Amyloid Microclots and Capillary Diametersmentioning
confidence: 99%